Permanent magnet working point ripple in synchronous generators. Issue 5 (12th May 2017) - Sjökvist, Stefan; Rossander, Morgan; Eriksson, Sandra
Abstract : Permanent magnets (PMs) are today widely used in electrical machines of all sorts. With their increase in popularity, the amount of research has increased as well. In this study, the magnetic flux density ripple of the working point of the PMs in a 100 kW PM synchronous generator has been investigated for three different load cases: no load, AC load, and DC load. The PMs will be subjected to a shift in working point as a consequence of the characteristics of the electrical loading. This study is based on finite element method simulations where the ripple of the magnetic flux density in the PMs was recorded at three positions within a PM. The slot harmonic of 7.5 times the electrical frequency ( f el ) was present in the results for all load cases, but mainly at the surface of the PM, as expected. Results showed an unexpected harmonic of 1.5 f el, assumed to be an undertone of the slot harmonics. The 6 f el harmonic for the DC load case was significantly higher than for the AC load case and is caused by the current fluctuation during passive rectification. For the studied machine, the added harmonics in the magnetic field due to passive rectification are less than the slot‐related harmonics.